Motivation Levels of Administrative Employees at a Selected Government Department - Ashley Ntombi Bhuda; Cornelia Harmse (African Journal of Inter-Multidisciplinary Studies, 2025)
In regions across South Africa there is an urgent need for government departments to deliver high-quality services consistently. The efficient and timely delivery of government services to citizens is largely dependent on the critical role played by administrative employees. This study assessed the motivation levels among administrative employees within a selected government department. The study used Herzberg's Two-Factor Theory framework that distinguishes between intrinsic motivation (doing something for internal satisfaction or personal fulfilment) and extrinsic motivation (driven by external rewards such as salary, recognition or career advancement). The research primarily explored intrinsic and extrinsic factors influencing employee motivation, employing quantitative research methodology to assess the motivation levels of administrative employees. A structured questionnaire utilising a 5-point Likert scale was used to gather quantitative data. Initially, the preliminary study involving 20 administrative employees was conducted using a closed-ended questionnaire distributed through Google Forms. The reliability of the questionnaire constructs was assessed using Cronbach's alpha which yielded an overall alpha range of 0.70 to 0.95, indicating strong internal consistency among the items within each construct. As this study remains ongoing, conclusions will not be drawn solely from the preliminary study; instead, findings will be generalised to the entire population under investigation.